2005
DOI: 10.1016/j.jvs.2005.06.018
|View full text |Cite
|
Sign up to set email alerts
|

Rapamycin-coated expanded polytetrafluoroethylene bypass grafts exhibit decreased anastomotic neointimal hyperplasia in a porcine model

Abstract: Rapamycin-eluting ePTFE grafts decrease neointimal hyperplasia in a porcine model. Further studies are needed to evaluate whether patency will be improved. Rapamycin-eluting ePTFE grafts may allow the use of prosthetic grafts in situations in which autologous vein is unavailable and in which neointimal hyperplasia is pronounced, such as in small-diameter (<6-mm) vessels typical of infrapopliteal interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
35
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(37 citation statements)
references
References 36 publications
2
35
0
Order By: Relevance
“…Both the coagulation system and the inflammatory processes contribute to the development of this neointima, which is a proliferation of myofibroblasts with endothelial cell ingrowth. [3][4][5][6] The neointima is associated with organizing thrombus and tends to be most severe at the anastomotic sites. 7 Furthermore, these patients are uniformly cyanotic, and other growth factors such as vascular endothelial growth factor have increased expression in this patient group, potentially intensifying neointimal growth.…”
Section: Article P 293mentioning
confidence: 99%
“…Both the coagulation system and the inflammatory processes contribute to the development of this neointima, which is a proliferation of myofibroblasts with endothelial cell ingrowth. [3][4][5][6] The neointima is associated with organizing thrombus and tends to be most severe at the anastomotic sites. 7 Furthermore, these patients are uniformly cyanotic, and other growth factors such as vascular endothelial growth factor have increased expression in this patient group, potentially intensifying neointimal growth.…”
Section: Article P 293mentioning
confidence: 99%
“…[1][2][3] This fraction is expected to grow as both the incidence of repeat interventions and mean life spans of people increase. 4,5 Unfortunately, no current synthetic small-diameter grafts are suitable for CABG because they fail with high frequency due to thrombosis and intimal hyperplasia-both of which give rise to resistance to blood flow.…”
Section: Introductionmentioning
confidence: 99%
“…(3), where Q is the average rate of fluid flow and R is the average resistance between sampled points of pressure upstream (P purging ) and downstream (atmospheric pressure, P atm ) of a lumenal occlusion. (3) Grafts were loaded with fluid and allowed to cure for set times. The cured graft contents were then compressed at a constant rate until the graft contents were purged.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have indicated that the efficacy of rapamycin in stents might not persist for a long time period. 31,32 It has been suggested that even though retention of the drug could be detected at day 90, intimal proliferation could not be inhibited any further at this time point. 32 Therefore, the duration of effect of rapamycin in local tissue in vivo after ex vivo treatment needs further investigation.…”
mentioning
confidence: 99%
“…Moreover, no thrombosis or aneurysm occurred following treatment with RAP-PLGA-NP, which was in accordance with other studies. [18][19][20]31 The early thrombus occurring in some of the animals in our study might have been caused by manipulation rather than being an adverse effect of the drug. Previous studies have indicated that the efficacy of rapamycin in stents might not persist for a long time period.…”
mentioning
confidence: 99%